Collagen synthesis on ultraviolet A irradiated human skin fibroblast treated with insulin - Febrina Rismauli Panggabean Satiti Retno Pudjiati Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Ultraviolet (UV) irradiation from the sun can stimulate premature skin aging because UV irradiation inhibits collagensynthesis, promotes collagen degradation and inhibits fibroblast proliferation. Insulin is capable to stimulate fibroblastgenes collagen expression, DNA synthesis, and collagen synthesis. The effect of insulin in reducing collagen synthesisamong repeated-UVA irradiation on human skin fibroblast has never been studied. This study aims to investigate theeffect of insulin in collagen synthesis among repeated-UVA irradiation on normal human skin fibroblast. To asses thecollagen synthesis collagen degradation, collagen deposition and fibroblast proliferationweremeasured. Experimentalstudy was performed among passage 3 of fibroblast which was isolated from a circumcised skin of a 6-year-old boy.Fibroblasts were irradiated with 3 repeated exposurewith total cumulative dose 9000 mJ/cm2 and treated withinsulin 0.5; 1; 2 μg/mL and placebo. Cellswere then incubated for 48 hours, collagen degradation, collagen depositionand fibroblast proliferation were read colorimetric by using Spectroscopy 550 nm. The effect of insulin 0.5; 1 and2 ìg/mL in collagen synthesis among repeated-UVA irradiation on normal human skin fibroblast with cumulative dose9000 mJ/cm2 was not capable to reduce collagen degradation, nor capable to increase collagen and fibroblastproliferation. Insulin dose 0,5 μg/ml-2 μg/ml among repeated-UVA irradiation on normal human skin fibroblast wasnot capable to increase collagen synthesis.Key words: photoaging-DNA synthesis-proliferasion-aging process-gene expression